Addition of Fermented Biomass Combination of Pineapple Waste and Indigofera Leaves in Broiler Rations on Nutrient Digestibility in Vitro and In Vivo - Palupi, Rizki; Lubis, Fitri Nova Liya; Lena, Mirza; Anjani, Hikma Pralitha (Faculty of Agriculture, 2025)
This study aimed to evaluate the effect of adding fermented biomass from a combination of pineapple waste and Indigofera leaves on nutrient digestibility in broiler chickens, both in vitro and in vivo. The materials used included 21-day-old broiler chickens, finisher-phase broiler rations, pineapple waste, and Indigofera leaves. A completely randomized design (CRD) was applied, consisting of five treatments with three replications each. The treatments included different levels of fermented biomass addition to the broiler rations: P1= 100% pineapple waste, P2= 98% pineapple waste + 2% Indigofera, P3= 96% pineapple waste + 4% Indigofera, P4= 94% pineapple waste + 6% Indigofera, and P5= 92% pineapple waste + 8% Indigofera. The results showed that the addition of fermented biomass from pineapple waste and Indigofera leaves had a significant effect (P0.05) on increasing crude protein digestibility and crude fiber digestibility. In conclusion, incorporating fermented biomass of pineapple waste and Indigofera into broiler rations improves protein and fiber digestibility, with the optimal combination being 92% pineapple waste + 8% Indigofera.